Implementation of K-Means to Classify Poverty Based on Housing Characteristics in Central Java in 2021 - Setyaningsih, Laras Indah; Wulandari, Anjelina Rafika; Arum, Prizka Rismawati (Jurnal Pendidikan Matematika, 2023)
Poverty is a condition in which a person's inability to meet basic needs such as food, clothing, shelter, and education so that he is unable to guarantee his own survival. To support the successful implementation of development programs, especially those aimed at reducing poverty, grouping districts/cities using cluster analysis can be assisted. Cluster analysis can be carried out to identify how the poverty rate is based on housing characteristics in Central Java which can be taken into consideration so that development programs are more targeted. Cluster analysis is a grouping method in which a group has the same characteristics, while between groups have different characteristics. K-means is one of the algorithms in data mining that can be used for grouping/clustering. The purpose of this study was to determine the classification of poverty in Central Java districts/cities based on housing indicators which include the floor area of the house, building materials for the widest floor, sources of drinking water, main building materials for roofs, and main fuel for cooking. This study yielded three clusters, with cluster 1 consisting of 22 districts and cities, cluster 2 consisting of 5 districts and cities, and cluster 3 consisting of 8 districts and cities. Cluster 1 grouping indicators were based on the sources of drinking water and the type of fuel used for cooking, cluster 2 grouping indicators were based on the size of the house's floor plan, and cluster 3 grouping indicators were based on the materials used to construct the house's widest floor and its main roof. Kemiskinan merupakan kondisi dimana ketidakmampuan seseorang untuk memenuhi kebutuhan pokok seperti pangan, sandang, papan dan pendidikan sehingga tidak mampu menjamin kelangsungan hidupnya sendiri. Untuk menunjang keberhasilan pelaksanaan program-program pembangunan, khususnya yang ditujukan untuk mengurangi kemiskinan dapat dibantu dengan mengelompokkan kabupaten/kota dengan analisis cluster. Analisis cluster dapat dilakukan untuk mengenali bagaimana tingkat kemiskinan berdasarkan karakteristik perumahan di Jawa Tengah yang dapat dijadikan pertimbangan agar program-program pembangunan lebih tepat sasaran. Analisis cluster merupakan suatu metode pengelompokan dimana dalam suatu kelompok mempunyai karakteristik yang sama, sedangkan antar kelompok mempunyai karakteristik yang berbeda. K-means merupakan salah satu algoritma dalam data mining yang dapat digunakan untuk mengelompokkan/clustering. Tujuan penelitian ini ialah untuk mengetahui pengelompokan kemiskinan Kabupaten/Kota Jawa Tengah berdasarkan indikator perumahan yang meliputi luas lantai rumah, bahan bangunan untuk lantai terluas, sumber air minum, bahan bangunan utama untuk atap rumah, dan bahan bakar utama untuk memasak. Penelitian ini menghasilkan 3 cluster dengan cluster 1 memiliki anggota 22 Kabupaten/Kota, cluster 2 memiliki anggota 5 Kabupaten/ Kota, cluster 3 memiliki anggota 8 Kabupaten/Kota. Indikator pengelompokkan cluster 1 didasarkan kepada sumber air minum dan bahan bakar untuk memasak yang digunakan, indikator pengelompokan cluster 2 didasarkan kepada luas lantai rumah, sedangkan indikator pengelompokkan cluster 3 didasarkan kepada bahan bangunan untuk lantai terluas dan bahan bangunan utama untuk atap rumah.